Efficacy of non-invasive ventilation and oxygen therapy on immunocompromised patients with acute hypoxaemic respiratory failure: protocol for a systematic review and meta-analysis of randomised controlled trials - Juhong Shi; Gang Liu; Meng Wang; Tao Wang; Yi Li; Yi Yang; Xuezhong Yu; Huadong Zhu; Yong Ma; Zongru Li; Lixi Zhang; Kun He; et al. (BMJ Open)
Background The number of immunocompromised patients has increased in recent years. Acute respiratory failure is a common complication leading to intensive care unit (ICU) admission and high mortality among such patients. The use of non-invasive ventilation (NIV) or oxygen therapy among these patients remains controversial, according to the inconsistent results of several randomised clinical trials (RCTs). This meta-analysis aims to evaluate whether NIV or oxygen therapy is the more appropriate initial oxygenation strategy for the immunocompromised patients with acute respiratory failure.Method We will search all the RCTs that compared the efficacy of NIV and oxygen therapy on immunocompromised adult patients with acute hypoxaemic respiratory failure on the major databases (Cochrane Library, MEDLINE, EMBASE, Web of Science and others), conference proceedings and grey literature. Eligible RCTs will be included in accordance with the pre-specified eligibility criteria. The risk of bias will be assessed using the Cochrane Collaboration criteria and the quality of evidence will be assessed with the Grading of Recommendations Assessment, Development and Evaluation system. Data will be extracted with a standardised form and analysed using RevMan V.5.3 analyses software. Heterogeneity will be assessed using I2 statistic and the source of which will be investigated. Publication bias will be identified with the funnel plot.Ethics and dissemination Ethical approval is not required since it is not carried out in humans. The systematic review will be published in peer-reviewed journals and disseminated extensively through conferences.